The Effect of Stress Management Group Counseling on Stress in Women with a Family History of Breast Cancer - Elham Behnam-Talab; Farkhondeh Amin-Shokravi; Masoumeh Hashemian; Mahdi Moshki; Naeimeh Jafaei (Journal of Kerman University of Medical Sciences, 2015)
Background & Aims: Breast cancer is the most prevalent cancer and the leading cause of death due to cancer in woman. The presence of a breast cancer patient in the family not only increases the risk of this cancer among family members, but can also increase their stress level. Moreover, increased stress level can be proposed as a trigger for breast cancer. The aim of the present study was to evaluate the effect of stress management group counseling on stress levels of women with a family history of breast cancer. Methods: This was a quasi-experimental study with control group. In this study, 97 women whose mothers, sisters, or daughters had breast cancer in the past 5 years were selected and randomly divided into control and experimental groups. The stress management intervention was designed in the form of group counseling and implemented in 6 sessions lasting 90 minutes. The data collection tool consisted of a 2-part questionnaire including a demographic questionnaire and the Harry’s stress questionnaire. The questionnaire was completed by both group participants before and after the intervention. Data were analyzed using independent t-test in SPSS software. Results: Before the intervention, no significant statistical difference was observed between the two groups in terms of the mean stress score. However, after the intervention, independent t-test showed a statistically significant difference between the control and experiment groups in terms of the mean stress management score (P < 0.001) Conclusion: Stress management group counseling is effective on the stress level of women with a family history of breast cancer. Thus, this intervention is recommended as an appropriate mental health plan in this group of women